Perbedaan status fungsional pasien stroke saat masuk dan keluar ruang rawat inap Rsud arifin achmad - Sherly - Fandri; Wasisto - Utomo; Ari Pristiana Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of this research was to describe the differences of functional status between stroke patients which coming and exiting in care unit at Arifin Achmad general hospital Pekanbaru. The design of this research was Analitic Descriptive with comparative study technique. In this study, researcher used consecutive sampling method with total number of respondents was 30. The instrument in this research was barthel index which consist of 10 items of assesment related capability in self care activities and mobilization. The data were analyzed by univariate and bivariate. The results showed the functional status of stroke patients which come to unit care had very severe disabality (50%) and functional status of stroke patients which exit from unit care had very severe disability (43.3%). Based on the marginal homogenity test, it can concluded that there was a differences of functional status between stroke patients which coming and exiting in care unit at Arifin Achmad general hospital Pekanbaru with p value 0.025 (p value < α). It is necessary for nurse to increase there knowledge about functional status of stroke so the quality of health services and can be given optimally. Keyword : Functional status, stroke.